Tubular CD44 plays a key role in aggravating AKI through NF-κB p65-mediated mitochondrial dysfunction - Jiewu Huang; Ping Meng; Ye Liang; Xiaolong Li; Shan Zhou; Jiemei Li; Xiaoxu Wang; Jinhua Miao; Weiwei Shen; Lili Zhou (Cell Death and Disease)
Abstract Acute kidney injury (AKI) is in rapid prevalence nowadays. Of note, the underlying mechanisms have not been clarified. Several reports showed a cluster of differentiation-44 (CD44), a cell-surface glycoprotein, might be involved in AKI. However, its role in AKI has not been clearly clarified. Herein, we found CD44 increased in renal tubules in AKI mice. Gene ablation of CD44 improved mitochondrial biogenesis and fatty acid oxidation (FAO) function, further protecting against tubular cell death and kidney injury. Conversely, ectopic CD44 impaired mitochondrial homeostasis and exacerbated tubular cell apoptosis to aggravate AKI progression. From transcriptome sequencing, we found that CD44 induces mitogen-activated protein kinase (MAPK) and NF-κB p65 signaling. Lipidomics also showed that CD44 interfered with multiple aspects of lipid metabolism. We deeply investigated NF-κB p65 inhibited the transcription of peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC-1α), resulting in mitochondrial dysfunction and cell apoptosis. CD44 also facilitated iron intake to assist cell ferroptosis. Hence, our study provided a new mechanism for AKI, and demonstrated that targeted inhibition on CD44 could be a promising therapeutic strategy to resist AKI.